2017
DOI: 10.20944/preprints201702.0022.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PHB Production in Biofermentors Assisted through Biosensor Applications

Abstract: Polyhydroxyalcanoates (PHAs) are biodegradable polymers synthesized in cytoplasmic granules in bacteria, such as Cupriavidus necator (Ralstonia eutropha), Alcaligenes latus, Pseudomonas spp., Comamonas spp. and other species. PHAs accumulation occurs in response to stress conditions, i.e. under high carbon and low nitrogen (24:1 ratio). PHA can be synthesized using recombinant microorganisms (provided with the operon phbA/phbB/phbC), escaping the constrains of nutrient request, except addition of high amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…26 A quantitative measure of PHA producing bacteria has been based on fluorescence scale reads using a laser scanner. 31 (Figure 1) In our hands, the system showed an optimization of feed stock consumption and determination of feed supplementation during exponential growth that occurred contemporary to PHB synthesis, while at the stationary phase determination of maximum PHB presence allowed to stop the biofermentor without further supplementation of feeds. In this way, we obtained an improvement of bacteria growth phase monitoring, in respect to the available systems.…”
Section: Biosensors For Automatic Monitoring Of Fermentation Processmentioning
confidence: 95%
See 1 more Smart Citation
“…26 A quantitative measure of PHA producing bacteria has been based on fluorescence scale reads using a laser scanner. 31 (Figure 1) In our hands, the system showed an optimization of feed stock consumption and determination of feed supplementation during exponential growth that occurred contemporary to PHB synthesis, while at the stationary phase determination of maximum PHB presence allowed to stop the biofermentor without further supplementation of feeds. In this way, we obtained an improvement of bacteria growth phase monitoring, in respect to the available systems.…”
Section: Biosensors For Automatic Monitoring Of Fermentation Processmentioning
confidence: 95%
“…Finally, solid PHB/PHA is obtained by non-solvent (methanol and water 7:3vol/vol) precipitation (five volumes for each volume of chloroform) followed by filtration. 31…”
Section: Pha Quantification and Extractionmentioning
confidence: 99%
“…Another study reported that the Chlamydomonas reinhardtii triglycerol was molded as bioplastic beads that could withstand 1.7 MPa of compressive stress [ 73 ]. Acetate and citrate supplementation in the media is another strategy to improve the PHB production in cyanobacteria and microalgal cells [ 74 ]. Strain improvement such as mutation and genetic modification of key enzymes involved in the PHB synthesis pathway can enhance PHB production [ 75 ].…”
Section: Biorefinerymentioning
confidence: 99%
“…A sample was collected from a station (activated sludge) located at Pajam, Shubra El-Kheima, Qalyubia, Egypt. For bacterial isolation, 11 the sludge sample was serially diluted up to 10 −6 . 100 μL from each dilution was cultured on carbon-rich nutrient agar medium composed of 10 g L −1 glucose, 8 g L −1 NaCl, 5 g L −1 peptone, 3 g L −1 yeast extract and 15 g L −1 agar; 19 the pH was adjusted to 7 using 1 mol L -1 NaOH and 30% HCl.…”
Section: Sample Collection and Bacterial Isolationmentioning
confidence: 99%
“…2 The formation of the polymer is mainly associated with the stationary phase of many bacterial strains such as Bacillus cereus, Bacillus subtilis, Brevibacterium halotolerance and Pseudomonas aeruginosa [8][9][10] ; acetyl coenzyme A (acetyl-CoA), the intermediate of the central carbon metabolism, is required for cell synthesis during the exponential phase but is diverted to produce PHAs in the stationary phase. 11 PHA granules are made up of a hydrophobic, amorphous polymeric core enclosed by a single layer of phospholipids as well as protein molecules. 12 These proteins involve the PHA synthase and intracellular PHA depolymerase.…”
Section: Introductionmentioning
confidence: 99%